(untitled) (Annals of Medical Research, 2022)
Aim: The purpose of the present study was to investigate in vitro the effect of agomelatine, an analog of melatonin, on potassium chloride-stimulated contractions (KCl) in duodenum, jejunum, ileum, and colon in rats. Materials and Methods: A total of 7 Wistar albino female rat strips were used in the study. Rats were 8-10 weeks old and weighed 200-250 g. After the rats were decapitated without anesthesia, duodenum, jejunum, ileum, and colon strips were prepared and placed in the organ bath. Agomelatine was applied in doses of 100, 200, and 1000 μM to the strips that were contracted with KCl (80 mM). Then, 1000 μM agomelatine was applied after preliminary treatment of melatonin receptor antagonist luzindole (1 μM) to investigate the action mechanism of agomelatine on intestinal smooth muscles. The records were analyzed before and after each dose, and frequency, peak to peak (P-P) and area values were compared. Results: Agomelatine inhibited the KCI- induced contractions in duodenum, jejunum, ileum, and colon strips in a dose-dependent manner. Depending on the agomelatine application, the frequency, “P-P”, and the area values under the curve decreased at statistically significant levels (p<0.05). However, the effect of agomelatine decreased at significant levels as a result of luzindole treatment (p<0.05). Conclusion: The dose-dependent inhibitor effect of agomelatine on KCl-stimulated contractions in the rat intestinal smooth muscle was shown for the first time in this study. Agomelatine was found to affect the smooth muscles of the intestines through melatonin receptors. This result suggests that agomelatine might have therapeutic potential in diseases in which gastrointestinal motility is impaired.